2020
DOI: 10.1016/s0140-6736(19)32990-3
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral therapy alone versus antiretroviral therapy with a kick and kill approach, on measures of the HIV reservoir in participants with recent HIV infection (the RIVER trial): a phase 2, randomised trial

Abstract: kill' strategy, for future trials significant enhancement of both 'kick' and 'kill' agents will be required. Research in context panel Evidence before this study This randomised clinical trial was designed to test the concept of 'kick and kill' as a strategy to achieve a cure for HIV infection. Prior to this study, there was evidence from in vitro and single arm clinical studies that the histone deacetylase inhibitor (HDACi) class of drugs could induce viral transcription from latently infected cells, potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
99
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 35 publications
(68 reference statements)
0
99
3
1
Order By: Relevance
“…HIVconsv immunogen consists of a chimeric protein assembled from 14 highly conserved domains derived from HIV-1 genes Gag, Pol, Vif, and Env alternating, for each domain, the consensus sequence of the four major HIV-1 clades A, B, C, and D (12). Upon delivery to both HIV-1-negative and positive individuals by heterologous prime/boost regimens as DNA or in simian adenovirus of chimpanzee (ChAdV) and poxvirus MVA vectors, HIVconsv vaccines were safe and induced CD8 + T cells with broad inhibitory capacity of HIV-1 in vitro, but showed no effect on the viral reservoir (16)(17)(18)(19)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…HIVconsv immunogen consists of a chimeric protein assembled from 14 highly conserved domains derived from HIV-1 genes Gag, Pol, Vif, and Env alternating, for each domain, the consensus sequence of the four major HIV-1 clades A, B, C, and D (12). Upon delivery to both HIV-1-negative and positive individuals by heterologous prime/boost regimens as DNA or in simian adenovirus of chimpanzee (ChAdV) and poxvirus MVA vectors, HIVconsv vaccines were safe and induced CD8 + T cells with broad inhibitory capacity of HIV-1 in vitro, but showed no effect on the viral reservoir (16)(17)(18)(19)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…The GRIN immunogen was a fusion of full-length Gag, Reverse Transcriptase (RT), Integrase and Nef, and was delivered by replication-deficient human adenovirus serotype 35 (Ad35-GRIN or A) [ 66 , 67 ]. Ad35-GRIN substituted for the simian adenovirus serotype 63-vectored HIVconsv vaccine used in previous trials [ 50 , 56 , 57 , 58 , 59 ], to which we lost freedom to operate following GlaxoSmithKline acquisition of the ChAdV63 vaccine vector. GRIN had an extensive sequence match to HIVconsv as GRIN covered almost 80% of all HIVconsv ( Figure 1 ) [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, our working hypothesis postulates that focusing vaccine-elicited T cells on the functionally conserved regions of HIV-1, which are common to most global variants and are hard to mutate, will be effective in slowing and controlling HIV-1 infection [ 41 , 42 , 43 , 50 , 51 , 52 , 53 , 54 , 55 ]. These regions contain epitopes typically subdominant in natural HIV-1 infection, but are capable of inducting robust T-cell responses when delivered by a potent vaccination regimen [ 50 , 56 , 57 , 58 , 59 , 60 ]. Such vaccine-elicited responses thus represent a rich source of previously undescribed, potentially important epitopes [ 61 , 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, dependency on cell-mediated and humoral immune responses that are already compromised in HIV-infected individuals because of impaired CD4+ T cell help and exhausted immune compartments poses a considerable obstacle to these strategies. Indeed, early results from combinatorial clinical trials which combine LRAs and immune-enhancing clearance strategies demonstrated that although HIV-1-specific immune responses were induced, no decrease in the size of viral reservoir or viral control in the absence of cART were observed (8)(9)(10) , reviewed in 11 ).…”
Section: Introductionmentioning
confidence: 99%